Differentially expressed proteins associated with fusarium head blight resistance in wheat - Zhang, Xianghui; Fu, Jianming; Hiromasa, Yasuaki; Pan, Hongyu; Bai, Guihua (My University, 2014)
Background: Fusarium head blight (FHB), mainly caused by Fusarium graminearum, substantially reduces wheat grain yield and quality worldwide. Proteins play important roles in defense against the fungal infection. This study characterized differentially expressed proteins between near-isogenic lines (NILs) contrasting in alleles of Fhb1, a major FHB resistance gene in wheat, to identify proteins underlining FHB resistance of Fhb1. Methods: The two-dimensional protein profiles were compared between the Fusarium-inoculated spikes of the two NILs collected 72 h after inoculation. The protein profiles of mock- and Fusarium-inoculated Fhb1+NIL were also compared to identify pathogen-responsive proteins. Results: Eight proteins were either induced or upregulated in inoculated Fhb1+NIL when compared with mock-inoculated Fhb1+NIL; nine proteins were either induced or upregulated in the Fusarium-inoculated Fhb1+NIL when compared with Fusarium-inoculated Fhb1−NIL. Proteins that were differentially expressed in the Fhb1+NIL, not in the Fhb1−NIL, after Fusarium inoculation included wheat proteins for defending fungal penetration, photosynthesis, energy metabolism, and detoxification. Conclusions: Coordinated expression of the identified proteins resulted in FHB resistance in Fhb1+NIL. The results provide insight into the pathway of Fhb1-mediated FHB resistance.
Citation: Zhang, Xianghui, Jianming Fu, Yasuaki Hiromasa, Hongyu Pan, and Guihua Bai. “Differentially Expressed Proteins Associated with Fusarium Head Blight Resistance in Wheat.” PLOS ONE 8, no. 12 (December 20, 2013): e82079. https://doi.org/10.1371/journal.pone.0082079.
Keywords: Fusarium head blight; Fusarium graminearum; Wheat; Fhb1; Proteins